Characterising gait in paediatric neuromuscular disorders: an observational study of spatio-temporal gait in a clinical cohort. Issue 23 (6th November 2022) - Kennedy, Rachel A.; de Valle, Katy; Adams, Justine; Ryan, Monique M.; Fitzgerald, Alisha K.; Carroll, Kate
Abstract: Aim: Few studies have characterised the relationship between disease and gait function in children and young people with rare neuromuscular disorders (NMDs). This study aimed to describe the relationship between disease and gait in a large paediatric cohort from a neuromuscular outpatient clinic. Methods: A prospective, cross-sectional study of gait in independently ambulant children and young people aged 4–21 years with a clinical or genetically confirmed NMD. Participants traversed an electronic walkway barefoot and in footwear at self-selected and fast pace. Analysis of disease included a typically developing (TD) reference group. Results: A sample of 113 participants with NMD, mean age 9.5 years (SD 3.1), 28% female, grouped into nine diagnostic subgroups. Eighty percent reported limitations to functional mobility. Children with NMD walked slower, with a shorter and wider step compared to a TD reference group, with moderate to large effect sizes for each of these gait parameters indicative of the clinical significance of these gait deviations. Children with Duchenne muscular dystrophy (DMD) walked slowest with a markedly wide gait pattern. Footwear had little overall effect on gait in children with NMDs. All children could accelerate over short distances. Conclusions: Gait, notably speed, step length, and width are clinically significant biomarkers of disease in paediatric NMDs, affording objective functional measures in clinical settings and research. Implications for rehabilitation: Gait should be considered a functional biomarker of disease in children and young people with neuromuscular disorders (NMDs). Comparison of gait in a paediatric neuromuscular cohort indicates that children with Duchenne muscular dystrophy (DMD) walk slowest with a shorter step length and a wider step width which increases with age and disease progression. Measurement of gait speed is a simple, pragmatic tool to monitor disease progression in the outpatient clinical environment and relates to everyday function. In clinical research, gait can be measured as a functional outcome to demonstrate change from disease-modifying interventions and treatments in NMDs.